Histories of the Middle East: Studies in Middle Eastern Society, Economy, and Law in Honor of A. L. Udovitch By Roxani Eleni Margariti, Adam Sabra, and Petra M. Sijpesteijn, eds. (Leiden: Brill Academic Publishers, 2010. 282 pages.) (American Journal of Islam and Society, 2012)
This collection of papers, presented at a Princeton University conference heldin May 2008, opens with an extensive bibliography of Abraham L. Udovitch’sworks and a preface detailing his scholarship on the medieval Islamic world’seconomic institutions, social structure, legal theory, and practices. The prefacealso highlights Udovitch’s role and scholarly contributions, prolific publicationsand international academic collaboration, his respect for interdisciplinaryexamination and combination of various methods, as well as the diversity ofhis intellectual pursuits and teachings. The editors praise his visionary approachof focusing on seemingly unconnected texts to uncover the past, suchas combining normative legal texts with narratives from diverse sources andgenres. His students, as demonstrated in this volume, have adopted these methods.Udovitch’s role in changing the writing of medieval Islamic history islauded, as is his encouragement to explore new techniques and methodologiesas well as his attention to the human experience within history.Mark Cohen, whose introduction examines Udovitch’s many roles (viz.,scholar, leading historian, activist, and teacher) provides a biography focusedon the professor’s life and projects. The nine essays, loosely grouped into fourunmarked categories, discuss the main areas of Udovitch’s interests: (1) “EconomicHistory” highlights the intersections between the legal theory of commerceand the commercial practices of institutions. It includes contributionsby Petra Sijpesteijn and Michael Bonner; (2) “Social History” relates economicand social actions, underlines their thematic and methodological commonalities,and comprises essays by Adam Sabra and Jonathan Berkey; (3)“Mediterranean and Indian Ocean” deals with “Middle Eastern History in itsGeographic contexts” and coalesces around what has been termed Udovitch’s“Mediterraneanist” concerns, namely, interdenominational relations and negotiationsbridging the gap between “rigid principles and supple accommodation.”This includes contributions by Olivia Remie Constable, YossefRapaport, and Hassan Khalilieh; and (4) “Urbanism,” the study of cities assites of economic exchanges and interactions between individuals and groups,combining legal, political, ideological, and intellectual dimensions to formthe realities of daily life. This includes two contributions by Boaz Shoshanand Roxani Margariti ...